Correction: A bioenergetic mechanism for amoeboid-like cell motility profiles tested in a microfluidic electrotaxis assay. Issue 11 (12th October 2017) - Peretz-Soroka, Hagit; Tirosh, Reuven; Hipolito, Jolly; Huebner, Erwin; Alexander, Murray; Fiege, Jason; Lin, Francis
Abstract : Correction for 'A bioenergetic mechanism for amoeboid-like cell motility profiles tested in a microfluidic electrotaxis assay' by Hagit Peretz-Soroka et al., Integr. Biol., 2017, DOI: ; Web:10.1039/c7ib00086c .